Difabike Approach in Empowering People With Disabilities Using Group Dynamics - Dyaloka Puspita Ningrum; Latifa Zahra (Universitas Ahmad Dahlan, 2021)
People with disabilities are still a vulnerable and marginalized group in society because of each individual's limitations. On the other hand, they also have sufficient knowledge and skills. The humanistic psychological approach to humanizing humans is the basis that can minimize negative issues that hit the group by using Activity Interaction Sentiment Theory. In collecting the data, this research uses qualitative descriptive by interviewing the founders of the Difabike fleet, drivers, and local officials to triangulate the data. This study shows that stakeholders are still struggling with stagnant development and focus on skills training without ongoing assistance. Seeing this, the founder of the Difabike fleet took the initiative to improve group dynamics for people with physical disabilities. The difabike fleet applies a family pattern where the founder embraces its members to provide actualization to empower them and develop their potential.